Cerebral perfusion and blood–brain barrier assessment in brain trauma using contrast-enhanced near-infrared spectroscopy with indocyanine green: A review - Forcione, Mario (J Cereb Blood Flow Metab, 2020)
Contrast-enhanced near-infrared spectroscopy (NIRS) with indocyanine green (ICG) can be a valid non-invasive, continuous, bedside neuromonitoring tool. However, its usage in moderate and severe traumatic brain injury (TBI) patients can be unprecise due to their clinical status. This review is targeted at researchers and clinicians involved in the development and application of contrast-enhanced NIRS for the care of TBI patients and can be used to design future studies. This review describes the methods developed to monitor the brain perfusion and the blood–brain barrier integrity using the changes of diffuse reflectance during the ICG passage and the results on studies in animals and humans. The limitations in accuracy of these methods when applied on TBI patients and the proposed solutions to overcome them are discussed. Finally, the analysis of relative parameters is proposed as a valid alternative over absolute values to address some current clinical needs in brain trauma care. In conclusion, care should be taken in the translation of the optical signal into absolute physiological parameters of TBI patients, as their clinical status must be taken into consideration. Discussion on where and how future studies should be directed to effectively incorporate contrast-enhanced NIRS into brain trauma care is given.